Between the Heaven and Human Beings: On the Idea of the Heaven and the Transformation of Poetry in the Mid-Tang Dynasty - Liu, Shun (Cultural and religious studies, 2019)
The relationship between the Heaven and human beings is a central issue in the transformation of Confucianism in the Mid-Tang Dynasty. The discourses on the Heaven by Han Yu, Liu Zongyuan, and Liu Yuxi helped to promote the transformation and greatly influenced the transformation in literature. The differences in the poetry among the three authors may also be interpreted from the perspective of their perceptions of the Heaven—Han Yu’ s discourse on the Heaven focused on the enemy-relationship between the Heaven and human beings, so his poems always showed tension and loss. Liu Zongyuan was interested in the alienation between the heaven and human beings, so his poems were more rational and placid than Han Yu’s. However, Liu Yuxi’s discourse on the Heaven paid attention to the positive influence of the Heaven on human beings, and most of his poems were filled with reason. The changes in the relationship between the Heaven and human beings lead to the broadened themes, innovated vocabulary, diversified styles, and varied fresh imageries. Likewise, the relationship between the Heaven and human beings established in the Song Dynasty led accordingly to a new type of literature different from the Tang literature.